Prospects and costs for reactive power control in Sundom smart grid - Sirviö, Katja; Välkkilä, Lasse; Laaksonen, Hannu; Kauhaniemi, Kimmo; Rajala, Arto (IEEE, 2018)
New options to provide the technical ancillary services locally and system-wide by distributed energy resources (DER) are needed in the future. Sundom Smart Grid (SSG), local smart grid pilot in Vaasa, offers a novel research platform to develop protection and control solutions for future distribution networks. In this study, an ancillary service solution for reactive power management was studied by utilizing measured data and available MV and LV network connected DER units. Different requirements for reactive power flow between distribution and transmission network were considered in the studies. Based on these requirements “Future Reactive Power Window” was formulated for SSG. The reactive power flow across voltage levels in different cases was studied by simulations. Simulations showed that a coordinated reactive power management scheme across different voltage levels is very important from the technical and the economical point of view for development of future distribution networks.
Keywords: smart grid; microgrid; active network management; reactive power control; fi=Sähkötekniikka|en=Electrical Engineering|